Nguyễn Đạt
Giới thiệu về bản thân
Chào mừng bạn đến với trang cá nhân của Nguyễn Đạt
0
0
0
0
0
0
0
2025-01-22 07:31:49
a) \(\dfrac{5}{4}\)-(\(\dfrac{1}{2}\))2=\(\dfrac{5}{4}\)-\(\dfrac{1}{4}\)=1
b) \(\dfrac{2}{3}\).\(\dfrac{-3}{2}\)+\(\dfrac{-7}{2}\).\(\dfrac{2}{3}\)
=\(\dfrac{2}{3}\).(\(\dfrac{-3}{2}\)+\(\dfrac{-7}{2}\))
=\(\dfrac{2}{3}\).(-5)
=\(\dfrac{-10}{3}\)
c)(\(\dfrac{1}{5}\)+\(\dfrac{4}{13}\))+(\(\dfrac{-2}{5}\)+\(\dfrac{7}{13}\))-(\(\dfrac{4}{5}\)-\(\dfrac{2}{13}\))
=\(\dfrac{1}{5}\)+\(\dfrac{4}{13}\)-\(\dfrac{2}{5}\)+\(\dfrac{7}{13}\)-\(\dfrac{4}{5}\)+\(\dfrac{2}{13}\)
=(\(\dfrac{1}{5}\)-\(\dfrac{2}{5}\)-\(\dfrac{4}{5}\))+(\(\dfrac{4}{13}\)+\(\dfrac{7}{13}\)+\(\dfrac{2}{13}\))
=(-1) + 1 = 0